Analysis of Zilvia Iskandar's Public Speaking Skills in The 2024 Vice Presidential Debate - Keke Wulandari; Andhika Pamungkas; Farida Hariyati (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study was titled to find out the public speaking ability of Moderator Zilvia Iskandar at the 2024 vice presidential candidate debate forum. The object of this study is the moderator's public speaking ability in the debate forum Candidate for vice presiddn 2024, the research method used is a qualitative method using a case study approach. The data collection techniques used by the authors in this study are interview, observation, and documentation techniques. The theory used in this study by Charles Henry is a speech technique, because basically a moderator also uses the speech techniques of Charles Henry's theory from modern rhetoric, using modern rhetoric aimed at developing effective communication skills. In a variety of situations, including public speech, debate, persuasive writing and interpersonal communication using force can be a follow-up study. The result of this study is the ability of public speaking to an influential moderator to conduct events, and can influence the audience to follow the moderator's directions, so that messages delivered by a moderator can be received by the listener. And from the research that's been done that public speaking as a whole is very good, everyone has characteristics in its speech delivery.